2014
DOI: 10.1158/1078-0432.ccr-13-3169
|View full text |Cite
|
Sign up to set email alerts
|

CADM1 Expression and Stepwise Downregulation of CD7 Are Closely Associated with Clonal Expansion of HTLV-I–Infected Cells in Adult T-cell Leukemia/Lymphoma

Abstract: Purpose: Cell adhesion molecule 1 (CADM1), initially identified as a tumor suppressor gene, has recently been reported to be ectopically expressed in primary adult T-cell leukemia–lymphoma (ATL) cells. We incorporated CADM1 into flow-cytometric analysis to reveal oncogenic mechanisms in human T-cell lymphotrophic virus type I (HTLV-I) infection by purifying cells from the intermediate stages of ATL development. Experimental Design: We isolated CADM1- and CD7-expressing peripheral blood mononucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 36 publications
8
119
0
1
Order By: Relevance
“…11,23 The coordinates have been deposited in the Gene Expression Omnibus database (GSE33615, GSE55851).…”
Section: Microarray Analysismentioning
confidence: 99%
“…11,23 The coordinates have been deposited in the Gene Expression Omnibus database (GSE33615, GSE55851).…”
Section: Microarray Analysismentioning
confidence: 99%
“…ATL cells often share the Treg phenotype, i.e., CD3 þ CD4 þ CD25 þ Foxp3 þ (8,9). Although ATL cells may be defined by their expression of CADM1 (10,11), the overlap and differences between Tregs and ATL cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, SBH can also detect monoclonal integration in a small percentage of HTLV-1 carriers and approximately 10% of HAM/TSP patients (42,43). Flow-cytometric analysis of T cells recently revealed that the expression of CADM1 and stepwise downregulation of CD7 were closely associated with the clonal expansion of HTLV-1-infected cells in ATL, and CADM1 þ cells with the downregulated expression of CD7 in asymptomatic HTLV-1 carriers exhibited common properties to those in indolent ATL carriers (44).…”
Section: Biology Of Htlv-1-associated Atlmentioning
confidence: 99%